Macrobenthos composition at the shoreline of Kislo-Sladkoye Lake, separating from the White Sea ... - Buvalyy, Semen; Garmaeva, Sanzhima; Mardashova, Maria; Krasnova, Elena; Menshenina, Larisa (EARSeL eProceedings, 2015)
Kislo-Sladkoye Lake is a unique model reservoir separating from the White Sea, which requires careful comprehensive interdisciplinary study of all characteristics. The lake is a subject of system-atic hydrological and hydrochemical surveys. An integral qualitative study of the macrozoobenthos at the shoreline of the lake has been conducted for the first time. Fourteen invertebrate macrozoo-benthic taxa were found. Mass species distribution boundaries were determined. Such marine an-imals as Mytilus edulis, Semibalanus balanoides, Littorina saxatilis, are only found at the marine side beyond the lake rapid. Brackish species show three distribution patterns: Gammarus duebeni, chionomids, Haliplus apicalis are met around the lake; Hydrobia ulvae, Chironomus salinarius, Enochrus halophilus are absent near the lake rapid; diptera larvae Setacera aurata are only found on slightly sloping coast parts. The collected data allowed us to map the lake zonation based on the species composition. Three zones are allocated: ...